Psychometric Properties of the Family Adaptability and Cohesion Evaluation Scale III in Latin American University Dental Students - Díaz-Narváez, Víctor; Reyes-Reyes, Alejandro; Erazo-Coronado, Ana María; Fortich-Mesa, Natalia; Estrada-Méndez, Nuvia; González-Martínez, Farith; Silva-Vetri, María; González-Díaz, Eugenia; Ulloque, María J.; Villalba, Silvina; Vilca, Lindsey W.; Calzadilla-Núñez, Aracelis; et al. (Puerto Rico Health Sciences Journal, 2024)
Objective: The Family Adaptability and Cohesion Evaluation Scale III (FACES III) is a self-report instrument that enables the assessment of the dimensions of adaptability and cohesion within a family, establishing whether or not that family is functional and classifying it according to categories within those dimensions. The objective of this research was to determine the psychometric properties of this instrument using a sample of dental students from 5 Latin American countries. Materials and Methods: The FACES III was administered to a sample of 2888 university dental students from Colombia (35.3%), Chile (34.6%), the Dominican Republic (19%), Argentina (6%), and El Salvador (5.1%). Confirmatory factor analysis was used to examine the factorial structure of the scale, comparing 3 models proposed in the Latin American literature, establishing a multigroup analysis to examine invariance among countries. Results: The results revealed a structure composed of 2 dimensions: cohesion and adaptability. These dimensions showed adequate structure and internal consistency. The invariance of the measurement model in the participating countries was confirmed. Conclusion: In general, this study offers evidence of the adequacy of the psychometric properties of FACES III in Colombian, Chilean, Dominican, Argentine, and Salvadoran dental students.